ANALYSIS AND ASSESSMENT OF WAGE TRENDS IN UKRAINE - YELISYEYEVA, OKSANA; KUTOVA, NATALIIA; STOLIETOVA, IRYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article is devoted to the analysis of wages as an economic category, as the main factor in the functioning of the labor market, an assessment of multiple indicators is carried out such as: annual average wage size dynamics and changes in the standard of the population living, taking into account inflationary processes. The index of real wages and the level of purchasing power of the population are analyzed. The assessment of the average monthly salary in the regions of Ukraine showed that in regions with a high average salary, it exceeds the new approved minimum only 1.8 times. The exception is the Dnipropetrovsk region, where the average wage is one of the highest (after Kiev, Donetsk and Kiev regions), and exceeds the minimum wage by 2.32 times, which is 20% better than in general about Ukraine. To analyze the dynamics of wages in Ukraine, forecasting of the average nominal wage was carried out using a multiplicative model of nonlinear autoregression of the fifth degree based on the input data of the five previous periods. An assessment of the average nominal wage based on the developed model showed that a decrease in the growth rate of nominal wages is expected in the near future, together with the identified trends (a decrease in real wages and a decrease in the gap between the minimum and nominal wages) indicates an increase in the crisis in Ukraine.